Augmenting Wireless Communication Performance through Signal Space Diversity and Reconfigurable Intelligent Surfaces - Yüce, İrem; Reşat, Mustafa Anıl; Özyurt, Serdar (Fırat University, 2025)
This study investigates the enhancement of the performance of single input single output communication systems, employing binary phase shift keying and quadrature phase shift keying modulation schemes, through the integration of signal space diversity (SSD) and reconfigurable intelligent surfaces (RIS). The study conducts a comparative analysis of analog and quantized RIS configurations under Rayleigh fading conditions. The findings reveal that both architectures significantly improve the bit error rate performance relative to conventional non-RIS-assisted systems. Specifically, the analog RIS configuration demonstrates greater resilience in mitigating error performance degradation, whereas the quantized RIS configuration exhibits higher susceptibility to phase distortions arising from quantization-induced inaccuracies. Furthermore, the incorporation of SSD results in a marked improvement in error performance while incurring only a minimal increase in system complexity. These results underscore the potential of integrating RIS and SSD as a cost-effective and energy-efficient solution, particularly in addressing the stringent reliability and performance requirements of 5G and beyond networks.

Bu çalışmada, ikili faz kaydırmalı anahtarlama ve dörtlü faz kaydırmalı anahtarlama modülasyon teknikleri için, işaret uzayı çeşitliliği (SSD) ve yeniden yapılandırılabilir akıllı yüzeyler (RIS) kullanan tek giriş tek çıkış sistemlerinin performansı araştırılmaktadır. Bu kapsamda, Rayleigh sönümlemeli kanallar altında analog ve nicemlenmiş RIS kurulumları karşılaştırılmaktadır. Her iki RIS yapılandırması da bit hata oranı performansını RIS olmayan sistemlere kıyasla önemli ölçüde artırmaktadır. Buna karşılık, analog RIS kurulumunun, nicemleme hataları sebebiyle ortam faz kaymalarından daha fazla etkilenen nicemlenmiş RIS kurulumuna kıyasla hata performansı üzerinde önemli ölçüde daha az etkisi olduğu görülmektedir. Bununla birlikte, SSD kullanımı sayesinde sadece çok küçük bir karmaşıklık artışıyla hata performansı oldukça iyileşmektedir. Bu açıdan, RIS ve SDD tekniklerinin birlikte kullanımı, 5G ve ötesi ağların taleplerini karşılamak için uygun maliyetli ve enerji verimli çözümler sağlama potansiyelini gerçekleştirebilecek bir alternatif olarak sunulmaktadır.
İşaret Uzayı Çeşitliliği ve Yeniden Yapılandırılabilir Akıllı Yüzeyler Aracılığıyla Kablosuz Haberleşme Başarımının Arttırılması
Keywords: Wireless Communication Systems and Technologies (Incl. Microwave and Millimetrewave); Kablosuz Haberleşme Sistemleri ve Teknolojileri (Mikro Dalga ve Milimetrik Dalga dahil)